Efektivitas Media Pembelajaran Berbasis Video Animasi Terhadap Hasil Belajar Fisika - Halmuniati Halmuniati*; Dedi Riswandi; Zainuddin Zainuddin; La Ode Asmin; La Isa (Program Studi Magister Pendidikan IPA Program Pascasarjana Universitas Syiah Kuala, 2022)
The lack of facilities and infrastructure, both laboratories and projectors, makes teachers rarely use learning media with methods that are still teacher-centered, making students limited in visualizing physical phenomena. This phenomenon has an impact on the difficulty in understanding physics so that their learning outcomes are included in the low category. Researchers in overcoming the problem using animated videos. The purpose of this study was to see the effectiveness of the application of animated videos in improving physics learning outcomes for class XI at SMAN 9 Kendari. This research is a quantitative research with a quasi-experimental method with a nonequivalent control group design. The research sample was determined by purposive sampling technique which was divided into 2 classes, namely the experimental class and the control class. The data analysis technique used is the independent sample t-test. The results of the study found that the use of animated video-based learning media was very effective to be applied to the physics learning process as seen from the provision of posttest questions and the gain test value also increased by 0.69 in the experimental class and 0.62 in the control class which was included in the medium category. So it can be concluded that animated video media is effective in improving physics learning outcomes